NEAT1: A Novel Long Non-coding RNA Involved in Mediating Type 2 Diabetes and its Various Complications - Jia, Dengke; He, Yaping; Wang, Yaqi; Xue, Mengzhen; Zhu, Leiqi; Xia, Fangqi; Li, Yuanyang; Gao, Yan; Li, Luoying; Chen, Silong; Xu, Guangfu; Yuan, Chengfu (Current Pharmaceutical Design, 2022)
Background: Nuclear128;enriched abundant transcript 1 (abbreviated as NEAT1) is a long-chain noncoding RNA involved in various physiological and pathological processes. This study aimed to clarify the effect and molecule system of NEAT1 within non-alcoholic fatty liver disease (NAFLD) as well as type 2 diabetes (T2DM). Methods: In this review, current studies concerning mechanisms of NEAT1l, in the development of type 2 diabetes and its complications have been summarized and analyzed. Also, we searched the papers based on NEAT1 related to NAFLD. The related studies were obtained through a systematic search of Pubmed. Results: NEAT1 displays a close correlation with how T2DM occurs and develops, and it was confirmed to be significantly up-regulated in T2DM and its various complications (e.g., diabetics nephropathy, diabetics cardiomyopathy, diabetics retinopathy as well as diabetic neuropathy). Besides, NEAT1 is capable of impacting the occurrence, development and prognosis of NAFLD and T2DM. Conclusion: LncRNA NEAT1 is likely to act as a novel therapeutic target for T2DM and its complications. Moreover, non-alcoholic fatty liver disease is also correlated with NEAT1.
Keywords: therapeutic target